Amino acid transporters mediate autonomous delivery of nanoparticle vehicles into living plants - Xue Xia; Jiawei Dong; Aijie Li; Yanlin Wang; Yang Liu; Yingfang Zhu; Liang Xu; Zhiyang Jing; Jing Wang; Yan Zou; Shiyong Sun; Lu Wang; et al. (Nature Communications)
Abstract Presence of the cell wall and the lack of streamlined pathways for cellular delivery of external agents into plants is a core challenge of plant biotechnology and crop engineering development. However, both viral and bacterial transmission have their own restrictions and the few non-heavy metal nanodelivery platforms require external forces for tissue penetration. Such dependency limits any high-throughput application considering the large plant numbers to be treated in the field or even laboratory exercises. Herein, we demonstrate Aspartic acid (Asp) decorated poly(ethylene glycol)-block-poly(2-(diisopropylamino)ethyl methacrylate) (Asp-PEG-PDPA) copolymers assembled micelles (Asp/PDPA-NP), a platform that utilises amino acid transporters (AtAAP1 and AtLHT1) as receptors for clathrin-dependent endocytosis, freely translocate to release loaded cargo into various plant tissue/cell types in a species-independent manner within ≤10 minutes through simple spray or co-culture. As proof-of-concept, abscisic acid (ABA)-loaded Asp/PDPA-NP was tested for its efficacy to confer plant drought resistance. Asp/PDPA-NP@ABA reduced the effective ABA dose down to 1 nM (one million-fold) and elicited anti-drought potency in representative eudicot (soybean) and monocot (maize) crop species. Owing to its delivery efficiency, Asp/PDPA-NP holds promise as a potent carrier for diverse chemicals and biomolecules in plant systems.